Joint Property in Polygamous Marriages: Practical Experience in Religious Courts - Mansari, Mansari; Khairizzaman, Khairizzaman; Devy, Soraya; Wahyudani, Zulham; Sahara, Siti; Jusoh, Mohammad Kori bin (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Regulations on joint property in polygamous marriages are not specifically addressed in legislation. This legal vacuum creates legal consequences and uncertainty for the community. This study aims to analyze the regulations related to the mechanism for dividing joint property acquired in marriage and the essence of separating joint property in polygamy applications. This research uses normative legal research. The primary legal materials used are the Marriage Law, Court Decisions, and the Compilation of Islamic Law (KHI). The secondary legal materials include reference books, journals, and research results. Data analysis was conducted qualitatively. The results of the study show that the mechanism for dividing property in polygamous marriages is not specifically regulated in legislation. Existing regulations only stipulate that joint property is divided between widows and widowers, whether the marriage ends due to divorce or death. In practice, the division of joint property in Religious Courts can be categorized into two types: the separation of property directly stipulated in the decision on the application for polygamy and after the occurrence of divorce or the death of one party, based on the general principles in the Marriage Law and KHI. There is a need for the reconstruction of the Marriage Law to ensure legal certainty in the context of the division of joint property. [Abstrak: Pengaturan harta bersama dalam perkawinan poligami tidak diatur secara spesifik pembagiannya dalam peraturan perundang-undangan. Kekosongan hukum ini menimbulkan konsekuensi hukum serta ketidakpastian hukum bagi masyarakat. Kajian ini bertujuan untuk menganalisis pengaturan terkait dengan mekanise pemilihan harta bersama yang diperoleh dalam perkawinan dan hakikat pemilahan harta bersama dalam permohonan poligami. Penelitian ini menggunakan jenis penelitian hukum normatif. Bahan hukum primer yang digunakan yaitu UU Perkawinan, Putusan Pengadilan dan KHI. Bahan hukum sekunder yang digunakan yaitu buku referensi, jurnal dan hasil penelitian. Analisis data dilakukan secara kualitatif. Hasil penelitian menunjukkan mekanisme pembagian harta poligami belum diatur secara spesifik dalam peraturan perundang-undangan. Pengaturan yang ada hanya menentukan harta bersama di bagi kepada janda dan duda baik putusnya perkawinan maupun karena terjadinya perceraian. Pengalaman praktik pembagiannya harta bersama di Pengadilan Agama dapat dikategorikan menjadi dua yaitu pemilahan harta yang langsung dipilah dalam penetapan permohonan izin poligami dan pasca terjadinya perceraian maupun meninggal salah satu pihak dengan berpedoman pada prinsip umum dalam UU Perkawinan dan KHI. Perlunya rekonstruksi UU Perkawinan yang berdimensi kepastian hukum dalam konteks pembagian harta bersama.]